KARAKTERISTIK DAN HAKEKAT PERATURAN PERUNDANG-UNDANGAN HUKUM EKONOMI SYARIAH - Sisi Ade Linda; Zufriani Zufriani; Doli Witro (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2021)
The birth and formation of laws and regulations related to sharia economic law are based on the growing development of sharia financial institutions (LKS). The operation of Islamic financial institutions must, of course, be following Islamic principles, namely those based on the Qur'an and hadith. Then the formation of laws and regulations of sharia economic law is rooted in fiqh muamalah. The research method used in this study is library research using library data from books, scientific articles, and others. Data analysis techniques are condensation, data presentation, and concluding. The study results show that the legislation related to Islamic economics, especially in Islamic banking, is widely absorbed from the fatwa of the Indonesian Ulema Council (MUI). Almost all MUI fatwas were absorbed as the basis for forming the Sharia Banking Law. There are several characteristics of the Act, namely universal, maslahah, varied, fairness in transactions, and transparency.